Local climatic changes affect biodiversity responses to land use: A review. Issue 1 (22nd October 2019) - Williams, Jessica J.; Newbold, Tim
Abstract: Aim: Climate and land‐use change, the greatest pressures on biodiversity, can directly influence each other. One key case is the impact land‐use change has on local climatic conditions: human‐altered areas are often warmer and drier than natural habitats. This can have multiple impacts on biodiversity and is a rapidly developing field of research. Here, we summarize the current state of understanding on the impact that local climatic changes have on biodiversity responses to land‐use change, in particular looking at whether human‐altered land uses favour species with certain climatic niches. Location: Global. Methods: We review studies that have identified links between species' climatic niches and the habitats/land‐use types they inhabit. We also critically discuss the methods used to explore this topic (such as the estimation of fundamental vs. realized climatic niches), identify key knowledge gaps by reference to related macroecological literature and make suggestions for further work. Results: Assemblages of vertebrate and invertebrate species in numerous human‐dominated land uses have been found to have higher proportions of individuals affiliated with higher temperatures and lower precipitation levels than assemblages within natural habitats. However, uncertainty surrounds the mechanisms that underlie these observed differences between communities across land‐use types, and it remains unexplored as to whether these trends differ geographically or taxonomically. Main conclusion: Shifts are being observed within human‐altered land uses to communities with, on average, warmer and drier climatic niches. A better understanding of the effects of local climatic changes associated with land‐use change will enhance our ability to predict future impacts on biodiversity, identify the species most at risk from interactions between climate and land‐use change and set up suitable management and conservation plans.